The Large srh Family of Chemoreceptor Genes in Caenorhabditis Nematodes Reveals Processes of Genome Evolution Involving Large Duplications and Deletions and Intron Gains and Losses - Robertson, Hugh M. (Genome Research, 2000)
The srh family of chemoreceptors in the nematodeCaenorhabditis elegans is very large, containing 214 genes and 90 pseudogenes. It is related to the str, stl, andsrd families of seven-transmembrane or serpentine receptors. Like these three families, most srh genes are concentrated on chromosome V, and mapping of their chromosomal locations on a phylogenetic tree reveals 27 different movements of genes to other chromosomes. Mapping of intron gains and losses onto the phylogenetic tree reveals that the last common ancestral gene of the family had five introns, which are inferred to have been lost 70 times independently during evolution of the family. In addition, seven intron gains are revealed, three of which are fairly recent. Comparisons with 20 family members in the C. briggsae genome confirms these patterns, including two intron losses in C. briggsae since the species split. There are 14 clear C. elegans orthologs for these 20 genes, whose average amino acid divergence of 68% allows estimation of 85 gene duplications in the C. elegans lineage since the species split. The absence of six orthologs in C. elegans also indicates that gene loss occurs; consideration of all deletions and terminal truncations of srh pseudogenes reveals that large deletions are common. Together these observations provide insight into the evolutionary dynamics of this compact animal genome.[A truncated alignment of most annoted members of this protein family is available in Pfam v. 4.2 as family 7tm_5 (http://pfam.wustl.edu/); alignments of all translations are available as supplementary information at http://www.genome.org and can be opened with the program PAUP; alignments of all translations and genes are available athughrobe@uiuc.edu.]
10.1101/gr.10.2.192